Analysis of Hazardous and Toxic Waste Management in the Animal Feed Industry in Padang Pariaman Regency - Dwi Elvia Ningsih; Abdul Razak; Skunda Dilarosta (Science and Environmental Journal for Postgraduate, 2024)
Hazardous and toxic materials are commonly used in the production and non-production processes of the animal feed industry. Hazardous waste is the end product of hazardous use. Generators of hazardous waste must handle it in accordance with applicable regulations. Efficient handling of hazardous waste not only improves the company's image, but also benefits the surrounding community and employees. PT X's animal feed industry is one of the producers of hazardous waste. The generation of B3 waste is the result of non-production activities such as machine maintenance and office work. Analysis of PT X's hazardous waste management is the objective of this study. The findings show that PT X's hazardous waste management consists of identifying the source and type of hazardous waste, packaging and labeling, storing hazardous waste in temporary shelters (TPS), and transporting hazardous waste by licensed third parties. Related to hazardous waste management activities, PT X has fulfilled all licensing requirements and complied with all applicable regulations.